اهتمام وتشجيع الوالدين نحو الممارسة الرياضية للأبناء وانعكاسه على الجوانب النفسية والاجتماعية لفئة المراهقين - بلقاسم دودو (Journal of Sport Science Technology and Physical Activities, 2025)
parental interest and encouragement of children in the practice of sports : Impact on the psychological and sociological aspects of adolescents . Family plays an Important role in the participation of their children to sport activities , it is one of the most Important institution which contribute to the social upbringing of the child in that it influences this behavior. Our present research is essentially motivated by the preoccupation to determine the nature of the relationship existing between the positive ( interest and encouragement ) of the parents toward the practice of sports activities by their children and the dimension of their psychological health. In the present research we applied the descriptive model we thought best adapted to the nature of our study. The tools we used were : personality testing t the secondary and intermediate levels of school (attia hanah) , and tow questionnaires were submitted to parents and children to measure the parental interest and encouragement for the practice of sports at school, a questionnaire to measure the parental the material and intellectual welfare of the study, a primary questionnaire our conception. The age of the elements of our sample ranged between (15-18) all of them secondary school pupils, 98 in number, male and female. We made sure to select our sample free from the variable of the dimension of psycho-social correspondence. We limited study to the period extending from October 2007 to June 2008. We also used the statistic tools: the calculating mean, the model deviation and the T test. Some of the main conclusions: 1- The absence of difference between males in the influence of parental interest and encouragement on the psychological and social sides during their scholarity . 2- There is a tight relationships between the parental interest and encouragement to practice sports activities and the psychological and social sides of the sample of our study.